Distance education in undergraduate nursing in the State of Rio de Janeiro: a sociocultural approach of structural markers - Preview note - Edmar Jorge Feijó; Claudia Mara de Melo Tavares
The present study deals with distance education in undergraduate nursing in Rio de Janeiro, whose general objective is to analyze the experiences in distance learning in undergraduate nursing in light of the sociocultural approach of mediated action. And the specific objectives are to map the experiences of distance education in undergraduate courses in nursing, to identify the educational models included in the proposals for distance learning and discuss the use of it in nursing education, analyzing the structural markers, limits and possibilities. There will be a documentary study of a quantitative and qualitative, grounded on the Institute of Studies and Research Anísio Teixeira, will be located where the higher education institutions that have degree in nursing accreditation in distance mode.